Multinationals do it better: Evidence on the efficiency of corporations' capital budgeting - Greene, William; Hornstein, A.; White, L. (Elsevier, 2009)
With U.S. multinational enterprises playing increasingly important roles in the global economy, it is important to understand the efficiency of their capital budgeting decisions. We examine an unbalanced panel of 332 U.S. firms from 1992-2000. Using the deviation of a firm's estimated marginal Tobin's q from a benchmark as an indicator of effective resource allocation, we find that widespread multinationals make more efficient capital budgeting decisions. We also test whether this reflects the MNEs' investment locations, but do not obtain support for the hypotheses that they might be monitored by more agents or more successfully resist pressures from interest groups and governments. © 2009 Elsevier B.V. All rights reserved.